SOLVABILITY OF NONLINEAR PERTURBED SYSTEM WITH UNBOUNDED CONTROL OPERATOR BY USING SUFFICIENTLYCONDITIONS OF ADMISSIBLE OBSERVATION OPERATORS - Hassan, Samir Kasim (MAGISTRA, 2013)
In this paper a sufficient conditions for the finite -time admissibility of an perturbed observation operator are given as sufficient estimate to prove the local existence , uniqueness of the mild solutions of nonlinear initial value input/output unbounded perturbed control/ observation problem in suitable Hilbert space using perturbed semigroup theory. Keyword: Perturbed semigroup, admissible , unbounded control, mild solution, strict contraction.